Sultling thinking strategy and its impact on improving the accuracy of some volleyball skills - Mariza , Mohammed; Abd al -Ilah , Maher; Abd , Mohannad (Journal of Physical Education, 2025)
This study aims to prepare practical volleyball lessons with a complex thinking strategy, and to identify the impact of volleyball strategy on the accuracy of the three volleyball skills (transmission from the bottom, the front preparation from the head, and receiving the two hands from below) for students, and I adopted the experimental research curriculum with the experimental design that The experimental and controlled groups with the control of the tribal and remote tests, for its suitability for the current research and its independent variable (the strategy of complex thinking) that applies to the students of the experimental group, while the students of the control group are applying the educational method used as it is in the physical education lesson, and the limits of the research community represented in the students of the second stage From the Faculty of Physical Education and Sports Science/Karbala University continuing to continue the morning study for the academic year (2023/2024), The total number of (92) students, who are inherently distributed in equal preparation to the four academic people, reached (23) students for each of them, in line with the achievement of the purposes of systematic research procedures. This society, which reached (46) students at (50%) of their origin society, represents the two research groups according to the commitment to the determinants of the aforementioned experimental design, and after identifying the tests, practical lessons in volleyball were prepared in this strategy and applied them by experimenting with the reality of two lessons per week for a period of (6) weeks Success, to be (4) practical lessons for each skill, and with a total of (12) educational units, and after the end of the experiment, the results of tribal and post tests were addressed with a system (SPSS), and The conclusions and recommendations were that it is possible to apply the vocabulary of the complex thinking strategy in practical physical education lessons for the second stage in the Faculty of Physical Education and Sports Science, and its application helps in improving the level of the accuracy of the three volleyball skills (transmission from the bottom, the front preparation from the head, and receiving hands From the bottom) among the second stage students in the Faculty of Physical Education and Sports Science, and they are aware of the improvements of its accuracy among students who learn without them in the practical lessons of volleyball, and it is necessary to generalize the results of this research when seeking to improve the accuracy of the three volleyball skills (transmission from the bottom, and the front preparation From above the head, and receiving hands from the bottom) among students of the second stage in the College of Physical Education and Sports Science, and it is necessary to focus on practical applications for strategies to stimulate students thinking more than explanation and guidance in the practical lessons of volleyball to increase students ’empowerment of practice and application based on the discovery Knowledge of the skill accuracy by the bridle thinking in it